Control of white mold of dry bean and residual activity of fungicides applied by chemigation - Miorini, Thomas J.J.; Raetano, Carlos G. [UNESP]; Everhart, Sydney E. (Elsevier, 2017)
Sclerotinia sclerotiorum is a necrotrophic fungal pathogen that causes white mold of dry bean (Phaseolus vulgaris L.). Chemigation with fungicides is used for disease control, but effectiveness of this application method and impact of irrigation level on residual fungicide activity in the plant over time under field conditions has not been well characterized. To assess the best method of application and fungicide for disease control, we conducted field studies in three field sites in São Paulo State in Brazil. Contact fungicide, fluazinam, was applied via center pivot at three irrigation levels (2.5, 5.1, 10.1 mm) at the Itaí field site in 2013. Fluazinam and procymidone (systemic) were independently applied via sprinkler at three irrigation levels (3.0, 4.5, 6.0 mm) in 2013 and four irrigation levels (2.5, 5.0, 7.5, 10.0 mm) in 2014 at the Pereiras field site. Fungicides were also applied at the Pereiras site using a backpack sprayer in 2014. Three successive fungicide applications were made at Pereiras in 2013 and two successive applications made at Pereiras in 2014. Three leaves from each treatment of the four replicated plots were collected in 2-day intervals after application, and fungicide residues assessed using a detached leaf bioassay. Lesion areas were used to estimate percent disease control. Regardless of fungicide or application method, disease control decreased over time (ANCOVA; P < 0.05). Area under the disease progress curve estimated from leaf lesion areas showed chemigation at the lowest irrigation level provided the best control in five of six trials of fluazinam and four out of five trials of procymidone. Ground applications were equally effective, showing no difference from chemigation at the lowest irrigation level in most comparisons. The percent reduction in number of S. sclerotiorum sclerotia, disease incidence and dry bean yield were evaluated at Pereiras in both years. Procymidone reduced the number of sclerotia formed. However, yield was only higher for treatments that included procymidone at Pereiras in 2013. Overall, results indicate that both lower irrigation level and ground application slow the loss of residual fungicide activity and reduce the total disease lesion area. Results from this study indicate that procymidone may be better able to reduce S. sclerotiorum sclerotia formation, which may be an important consideration for long-term disease management.
Keywords: Detached leaf bioassay; Fluazinam; Phaseolus vulgaris; Procymidone; Sclerotinia sclerotiorum